Answer:
W(e) = 6.02(50) = 301 lbs
Step-by-step explanation:
Ryan earned a yearly income of $67,000, he needed to pay an income tax of 17% . What was the amount of income tax he paid
Answer:
11,390
Step-by-step explanation:
67,000 x 17%= 11,390
Which conversions go from a smaller unit to a larger unit? Select all that apply.
centimeters to millimeters
decimeters to meters
hectograms to kilograms
liters to centiliters
Answer:
decimeters to meters
Step-by-step explanation:
There are 10 decimeters in a meter.
Answer:
decimeters to meters
hectograms to kilograms
Step-by-step explanation:
how do I write the expression (4f-3+2g)-(-4g+2) in standard form
Answer:
4f-5+6g
Step-by-step explanation:
129 times 6+1 pronto fast
Answer:
903
Step-by-step explanation:
Answer:
129 x 6=774
774+1=775
Step-by-step explanation:
Hope this helps
the slopes of two lines are 2 and -2. because of this we can conclude these two lines are which of the following?
Answer:
they also can be considerd perpendicular because they interset and make a 90 degree/right angle
Step-by-step explanation:
Solve this system:
2x+5y+z=3
x-3y+2z=2
-x+2y-3z=-7
Answer:
x= -3
y= 1
z= 4
Step-by-step explanation:
Please see the attached pictures for the full solution.
*I evaluated the determinants using Sarrus' rule (see last picture):
∆= aei +bfg +cdh -gec -hfa -idb
*The symbol '∆' (delta) is usually used to denote a determinant.
Someone help me please
Answer:
good luck
Step-by-step explanation:
Solve
3x + 8 = 2x + 21
Answer:
Step-by-step explanation:Simplifying
3x + 8 = 2x + -21
Reorder the terms:
8 + 3x = 2x + -21
Reorder the terms:
8 + 3x = -21 + 2x
Solving
8 + 3x = -21 + 2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
8 + 3x + -2x = -21 + 2x + -2x
Combine like terms: 3x + -2x = 1x
8 + 1x = -21 + 2x + -2x
Combine like terms: 2x + -2x = 0
8 + 1x = -21 + 0
8 + 1x = -21
Add '-8' to each side of the equation.
8 + -8 + 1x = -21 + -8
Combine like terms: 8 + -8 = 0
0 + 1x = -21 + -8
1x = -21 + -8
Combine like terms: -21 + -8 = -29
1x = -29
Divide each side by '1'.
x = -29
Simplifying
x = -29
3x + 8 = 2x + 21
3x - 2x + 8 = 21
x + 8 = 21
x = 21 - 8
x = 13
Given f (x) = -5x + 1, find f (6)
Answer:
x=6(given)
-5x+1
-5*6+1
-30+1
-29
hope this answer helps u
pls mark it as brainliest
A. y = 1x+2!
or
B. y = 1x - 21
Answer:
B.y=|x-2|
Step-by-step explanation:
y is equal to the modulus of x-2 two because in the graph the the line cut at -2
Factor: 3(5x+2)(5x-2)
. Find the coefficient of x3 in the expansion of (3+2x+x2)6
Answer: 9180
Step-by-step explanation:
(3 + 2x + x^2)^6 = x^12 + 12x^11 + 78x^10 + 340x^9 + 1095x^8 + 2712x^7 + 5284x^6 + 8136x^5 + 9855x^4 + 9180x^3 + 6318x^2 + 2916x + 729
This can be found using Pascal's Triangle.
The coefficient of x^3 is 9180.
.
3. Ada 7 to 3 times of a number will
give you 66 if that number is a
9
Answer:
Step-by-step explanation:
Let the no. be x
3 times the no. will be 3x
adding 7 to 3 times the no. will be 3x + 7
the result is 66 so it will be 3x + 7 = 66
Hope this helps
plz mark as brainliest!!!!!
Can someone do this for me ill give you brainliest
Answer:I think you make somthing like i think task one would be lets say (Av)task two would be like(Bx) and it would all end out like this C
Av+Bx=C
Step-by-step explanation:
The circumferences of earth is about 25,000 miles which is the circumference written in scientific notation
Answer:
2.5*10^4
I hope this helps
Answer:
2.5 x 10^4
this is a filler. I hope this helps though :)))))
Helps me solve this problem please please
IT LOOKS LIKE transtive:)))))
Answer:
D
Step-by-step explanation:
- (-6x + 6) + 3 = 3 + 4x
I need help
Answer:
x=3
Step-by-step explanation:
-1(-6x + 6) + 3 = 3 + 4x
6x - 6 + 3 = 3 + 4x
6x - 3 = 3 + 4x
2x - 3 = 3
2x=6
x=3
Answer:
x=3
Step-by-step explanation:
-(-6x+6)+3=3+4x
6x-6+3=3+4x
6x-3=3+4x
6x-4x=3+3
2x=6
x=6/2
x=3
final answer
thank you bro
X(x+5)+7(x+5)
Help please its for algebra class thanks for your support and your help thanks a lot
Answer:
x^2+12x+35Step-by-step explanation:
Let's simplify step-by-step.
x(x+5)+7(x+5)
Distribute:
=(x)(x)+(x)(5)+(7)(x)+(7)(5)
=x^2+5x+7x+35
Combine Like Terms:
=x^2+5x+7x+35
=(x^2)+(5x+7x)+(35)
=x^2+12x+35
Answer:
=x^2+12x+35
(0,0) is a solution to y> -3x + 4
Answer:
(0,0) is a solution.
Step-by-step explanation:
To see if this is true you can put (0,0) into the [tex]y[/tex] and [tex]x[/tex] variables like so: [tex]0>-3(0)+4[/tex]. When you solve this you get [tex]0>4[/tex] so this statement is true
Divide these polynomials.
(9x^3 + 9x^2 + 5x + 1) / (3x + 1)
Answer:
3x^2+2x+1
Step-by-step explanation:
Divide 9x^3+9x^2+5x+1 by 3x+1
Easy.
Solve for a
3a +1=4. With a 7 under it
Answer:
a=9
Step-by-step explanation:
(3a+1)/7=4
This deals with linear equations with one unknown.
Overview
Steps
Terms and topics
1 result(s) found
a=9
See steps
Step by Step Solution:
More Icon
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
(3*a+1)/7-(4)=0
Step by step solution :
STEP
1
:
3a + 1
Simplify ——————
7
Equation at the end of step
1
:
(3a + 1)
———————— - 4 = 0
7
STEP
2
:
Rewriting the whole as an Equivalent Fraction
2.1 Subtracting a whole from a fraction
Rewrite the whole as a fraction using 7 as the denominator :
4 4 • 7
4 = — = —————
1 7
Equivalent fraction : The fraction thus generated looks different but has the same value as the whole
Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator
Adding fractions that have a common denominator :
2.2 Adding up the two equivalent fractions
Add the two equivalent fractions which now have a common denominator
Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:
(3a+1) - (4 • 7) 3a - 27
———————————————— = ———————
7 7
STEP
3
:
Pulling out like terms
3.1 Pull out like factors :
3a - 27 = 3 • (a - 9)
Equation at the end of step
3
:
3 • (a - 9)
——————————— = 0
7
STEP
4
:
When a fraction equals zero
4.1 When a fraction equals zero ...
Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.
Now,to get rid of the denominator, Tiger multiplys both sides of the equation by the denominator.
Here's how:
3•(a-9)
——————— • 7 = 0 • 7
7
Now, on the left hand side, the 7 cancels out the denominator, while, on the right hand side, zero times anything is still zero.
The equation now takes the shape :
3 • (a-9) = 0
Equations which are never true:
4.2 Solve : 3 = 0
This equation has no solution.
A a non-zero constant never equals zero.
Solving a Single Variable Equation:
4.3 Solve : a-9 = 0
Add 9 to both sides of the equation :
a = 9
One solution was found :
a = 9
Hope this helps! Please mark Brainliest!
What is the value of x
Answer:
98 degrees
Step-by-step explanation:
First calculate the entire triangles angles:
180 - 53 - 45 = final angle of triangle
82 = final angle of triangle
Using the straight line rule for angles, x and the inner angle must equal to 180 degrees:
180 - 82 = x
98 = x
Angle x is 98 degrees.
8 in
6 in.
5 in.
Pls help
Answer:
this is volume, right?
Step-by-step explanation:
i have no idea though hahahahahah
frjghherhnetjhnjkg fgfhgheriugheriughierg
renjgregnjergjerbgg rehgbjregbjergjerbgj
What is the Nature of Roots of x^2+9x+14=0?
Answer:
(x+7)(x+2)
Step-by-step explanation:
If we multiply it out we get:
x * x = x^2
7 * x = 7x
2 * x = 2x
7 * 2 = 14
Add it all, we get: x^2 +9x+14
Therefore these are the factors
Does anyone know the answer to both of these questions??
find the slope y=-4x+3
Answer:
-4
Step-by-step explanation:
m=slope in y=mx+b
Answer:
-4
Step-by-step explanation:
y=mx+b
m=slope
b=y-intercept
-4=m(slope)
3=b(y-intercept)
Hope the graph wasn't to confusing :)
I hope this helps! :)
just a lil some some so please help me
Answer:
The answer to this is agree . Hope it helps.
Pls help me with this question
Answer:
option C, x=1
Step-by-step explanation:
[tex]2^{9x-3} = 8^{3-x}[/tex]
[tex]2^{9x-3} = (2^3)^{3-x}[/tex]
[tex]2^{9x-3} = 2^{9-3x}[/tex]
cut 2 from LHS and RHS you will get,
9x-3 = 9-3x
9x + 3x = 9 + 3
12x = 12
x = 12/12
x = 1
therefore, option C is the correct option
hope it helps you!
Answer:
[tex] \huge{ \boxed{ \bold{ \tt{x = 1}}}}[/tex]
Option C is correct.
Step-by-step explanation:
[tex] \text{First ,\: let's \: know \: about \: exponential \: equation} : [/tex]
Exponential EquationAn equation in which variables appears as an exponent of a base is known as exponential equation. The following axioms are useful while solving the exponential equations :
If [tex] \sf{ {a}^{x} = {a}^{b} }[/tex] , then x = bIf aˣ = 1 , then aˣ = a⁰ and x = 0Thus , while solving an exponential equation, we should simplify the equation till the equation is obtained in the form [tex] \sf{ {a}^{x} = {a}^{b}} [/tex] or aˣ = 1 .
Now, let's start to solve :
[tex] \sf{ {2}^{(9x - 3)} = {8}^{( 3 - x)}} [/tex]
➸ [tex] \sf{ {2}^{9x - 3} = {2}^{3(3 - x)} }[/tex]
➸ [tex] \sf{ {2}^{9x - 3} = {2}^{9 - 3x}} [/tex]
➸ [tex] \sf{ \cancel{2} ^{ \: 9x - 3} = \cancel{2} ^{ \: 9 - 3x} }[/tex]
➸ [tex] \sf{9x - 3 = 9 - 3x}[/tex]
➸ [tex] \sf{9x + 3x = 9 + 3}[/tex]
➸ [tex] \sf{12x = 12}[/tex]
➸ [tex] \sf{ \frac{12x}{12} = \frac{12}{12}} [/tex]
➸ [tex] \boxed{ \sf{x = 1}}[/tex]
The value of x is 1 .
Hope I helped!
Best regards! :D
~[tex] \text{TheAnimeGirl}[/tex]
Please help me with this! Legitimate answers only please!
Fill in the blanks with the proper/right options for the problem.
Answer:
x= amount of subscriptions
y= total amount
m= $5 rate of change
b= $15 a starting point....
Eq: y=5x+15
At a pumpkin patch, if Armando guesses the weight of his pumpkin within 0.3 pounds, he gets to take the pumpkin home for free. If his pumpkin weighs 4.9 pounds, which two equations can be used to find the minimum and maximum weights he can guess in order to get his pumpkin for free?
x – 0.3 = 4.9 and x – 0.3 = –4.9
x + 0.3 = 4.9 and x + 0.3 = –4.9
x + 4.9 = 0.3 and x + 4.9 = –0.3
x – 4.9 = 0.3 and x – 4.9 = –0.3
Please Help <3
Answer:
x – 4.9 = 0.3 and x – 4.9 = –0.3
Answer:
d
Step-by-step explanation: